Machine‐learning‐based outcome prediction in stroke patients with middle cerebral artery‐M1 occlusions and early thrombectomy. (21st December 2020) - Hamann, Janne; Herzog, Lisa; Wehrli, Carina; Dobrocky, Tomas; Bink, Andrea; Piccirelli, Marco; Panos, Leonidas; Kaesmacher, Johannes; Fischer, Urs; Stippich, Christoph; Luft, Andreas R.; Gralla, Jan; et al.
Abstract: Background and purpose: Clinical outcomes vary substantially among individuals with large vessel occlusion (LVO) stroke. A small infarct core and large imaging mismatch were found to be associated with good recovery. The aim of this study was to investigate whether those imaging variables would improve individual prediction of functional outcome after early (<6 h) endovascular treatment (EVT) in LVO stroke. Methods: We included 222 patients with acute ischemic stroke due to middle cerebral artery (MCA)‐M1 occlusion who received EVT. As predictors, we used clinical variables and region of interest (ROI)‐based magnetic resonance imaging features. We developed different machine‐learning models and quantified their prediction performance according to the area under the receiver‐operating characteristic curves and the Brier score. Results: The rate of successful recanalization was 78%, with 54% patients having a favorable outcome (modified Rankin scale score 0–2). Small infarct core was associated with favorable functional outcome. Outcome prediction improved only slightly when imaging was added to patient variables. Age was the driving factor, with a sharp decrease in likelihood of favorable functional outcome above the age of 78 years. Conclusions: In patients with MCA‐M1 occlusion strokes referred to EVT within 6 h of symptom onset, infarct core volume was associated with outcome. However, ROI‐based imaging variables led to no significant improvement in outcome prediction at an individual patient level when added to a set of clinical predictors. Our study is in concordance with current practice, where imaging mismatch or collateral readouts are not recommended as factors for excluding patients with MCA‐M1 occlusion for early EVT. Abstract : We used machine learning to investigate if region‐of‐interest‐based imaging variables improve individual prediction of functional outcome after early (<6 h) endovascular treatment (EVT) in large vessel occlusion stroke. Although a small infarct core was associated with good functional recovery, outcome prediction improved only slightly when imaging was added to patients' clinical variables. New imaging features need to be defined to improve outcome prediction for patients undergoing EVT in an early time window.28